2005
DOI: 10.4049/jimmunol.175.3.1677
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell Tolerance in Nonobese Diabetic Mice Is Restored by Insulin-Dependent Diabetes Resistance Alleles

Abstract: Although candidate genes controlling autoimmune disease can now be identified, a major challenge that remains is defining the resulting cellular events mediated by each locus. In the current study we have used NOD-InsHA transgenic mice that express the influenza hemagglutinin (HA) as an islet Ag to compare the fate of HA-specific CD8+ T cells in diabetes susceptible NOD-InsHA mice with that observed in diabetes-resistant congenic mice having protective alleles at insulin-dependent diabetes (Idd) 3, Idd5.1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…Another study subsequently found, unlike in other strains, transplantation tolerance to allogeneic skin grafts is not established in NOD mice by CD40/CD154 blockade accompanied by donor-specific transfusion of splenocytes (39). This may be explained in part by the finding that unlike the case in nonautoimmune prone control strains, peripheral CD8 T cells in NOD mice are relatively defective in ability to undergo deletion upon high levels of antigenic stimulation (40,41). Additionally, donorreactive CD8 T cells have been shown to be a barrier to establishment of allogeneic bone marrow chimerism (42).…”
Section: Establishing a Permanent T1d-protective State Of Mixed Allogmentioning
confidence: 92%
“…Another study subsequently found, unlike in other strains, transplantation tolerance to allogeneic skin grafts is not established in NOD mice by CD40/CD154 blockade accompanied by donor-specific transfusion of splenocytes (39). This may be explained in part by the finding that unlike the case in nonautoimmune prone control strains, peripheral CD8 T cells in NOD mice are relatively defective in ability to undergo deletion upon high levels of antigenic stimulation (40,41). Additionally, donorreactive CD8 T cells have been shown to be a barrier to establishment of allogeneic bone marrow chimerism (42).…”
Section: Establishing a Permanent T1d-protective State Of Mixed Allogmentioning
confidence: 92%
“…Because no genetic segregation analysis has been done previously to identify potential 129/Sv-derived Idd resistance loci, one might conjecture that a protective locus in the congenic region of Chromosome 5 may exist that interacts epistatically with another Idd in the Chromosome 7 region to boost protection to an extent even greater than seen in Chromosome 7 monogenic stocks carrying CBA or C57L alleles. Reports of synergistic (and sometimes unexpected) interactions among unlinked Idd regions are becoming more common, as for example, restoration of T cell tolerance (53) or induction of autoimmune biliary disease (54) in NOD bicongenic stocks.…”
Section: S4(b6)-art2amentioning
confidence: 99%
“…Islets were isolated as previously described (44). Briefly, pancreata were cut into small pieces using fine scissors and digested in 2 mg/ml collagenase P (Roche Diagnostics) and 2 g/ml DNase I (Roche Diagnostics) at 37°C for 20 min.…”
Section: Preparation and Administration Of Cytokine Complexes And Polmentioning
confidence: 99%